Contemporary industrial policy and challenges to South America and Brazil - CARLOS AGUIAR DE MEDEIROS; ESTHER MAJEROWICZ (Brazilian Journal of Political Economy)
ABSTRACT We seek to identify the major vectors reconfiguring contemporary industrial policy in the US and the European Union to inform policymaking in South America and Brazil given their specific challenges to economic development. We stress two main vectors, national security and environmental concerns, which have unleashed a tendency toward the nationalization or regionalization of supply chains through import substitution. They have also been grounding industrial policy on comprehensive planning embracing several sectors and activities. The essential question for South America and Brazil is to combine these concerns departing from a reality underpinned by deindustrialization, environmental degradation (deforestation), and social marginalization.